Free convection boundary layer flow over a horizontal circular cylinder in Al2 O3-Ag/water hybrid nanofluid with viscous dissipation - Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Fadhilah, Che Jamil; Ong, Huei Ruey (UTM Press, 2021)
In this paper, the mathematical model of free convection boundary layer flow of horizontal circular cylinder immersed in Ag/Water nanofluid and Al2O3-Ag/Water hybrid nanofluid are considered. The governing non-linear partial differential equations are first transformed to a more convenient way before being solved numerically using the Keller-box method. The numerical values for the reduced Nusselt number and the reduced skin friction coefficient are obtained and illustrated graphically as well as temperature profiles and velocity profiles. Effects of the Prandtl number, Eckert number and nanoparticle volume fraction are analyzed and discussed. It is found that the Nusselt number for Al2O3-Ag/Water hybrid nanofluid is comparable with Ag/Water nanofluid with a reduction in skin friction coefficient. The preliminary results reports here are important as a reference in exploring the potential of hybrid nanofluid to reduce the production cost compared to the used of metal nanofluid.